POTENTIAL OF PHOSPHATE SOLUBILIZING BACTERIA FROM MANGROVE RHIZOSFER EFFECT PLANT GROWTH CORN (Zea mays) - Nanda Anastia; Syafrina Sari Lubis (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2022)
Mangroves are an ecosystem that is inhabited by various kinds of organisms and microorganisms, one of which is phosphate solubilizing bacteria that can be isolated from the mangrove rhizosphere. This study used a completely randomized design (CRD) aimed to obtain isolates of Phosphate Solubilizing Bacteria (PSB) and test the potential for the growth of corn plants. There were 9 isolates of gram positive BPF and 1 gram negative BPF, all isolates were rod-shaped. The results of morphological and biochemical tests showed that 9 bacterial isolates are a group of the genus Bacillus with the code LSP 1, LSP 2, LSP 3, LSP 4, LSP 5, LSP 7, LSP 8, LSP 9, LSP 10 and the genus Pseudomonas with the code LSP 6 . Testing the value of the phosphate solubility index (IKF) found bacteria with the highest IKF values ​​of 33 mm and 23.25 with isolate codes LSP 1 and LSP 6. Medium IKF values ​​are 17.8 mm and 11.6 mm with isolate codes LSP 3 and LSP 5. The lowest IKF values ​​were 7.33 mm, 6.4 mm, 5 mm, 4.7 mm, 4.2 mm and 2.8 mm with isolate codes LSP 2, LSP 10, LSP 7, LSP 8, LSP 9, and LSP 4. Bacterial isolates with the highest IKF values ​​were inoculated on soil media for corn crop growth. LSP 1 bacteria was able to significantly affect the growth of corn plant height by 27.7 cm. Keywords: Phosphate Solubilizing Bacteria (BPF), Mangroves, Corn Plants